Psycological foundations to integrate the emotion in formative assessment - Torres Lizarazo, David Fernando; Monsalve Flórez, Jhon Alexánder (Rastros Rostros, 2021)
This reflexive article has as objective the theoretical analysis of emotions within the processes of formative assessment. To achieve this purpose, a documentary review is used, framed within the interpretive paradigm of social science. In the first place, the relationship between Revee’s theory and formative evaluation is developed; this process is connected, in the second instance, with Heller’s theory of feelings. In conclusion, the dialogue between formative assessment and emotion is rebuilt, as a starting point for the constructivist relationship among the teacher, the student and the educational institution, whose purpose is that the student reaches autonomy for their learning process